Quality As Competitive Advantage - Alghamdi, Hind; Bach, Christian (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Since 1970s quality has become a target for most organizations in the United States and most firms have spent millions of dollars on quality activities in order to reach defect-free productions [1]. This paper aims to discover how quality becomes a competitive advantage in different organizations. It includes some of the organizations that won Malcolm Baldrige Award in 2012 and shows what kind of criteria that made them qualified to win the award. The paper came up with a model called Performance Excellance shows the factor that lead to excellence performance in an organization. On the other hand, the paper aims to show what quality means from customers perspective. There is a survey conducted among 100 users of smartphones in order to discover what kind of features users prefer and is quality on of them or not. The results of the survey came up with the importance of quality from customers perspective. It shows that quality is one of the most important features users are looking for in a smartphone